1985
DOI: 10.1620/tjem.146.237
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prostaglandin E1 infusion in the pre-operative management of critical congenital heart disease.

Abstract: Prostaglandin E1(PGE1) was administered to 27 infants in whom pulmonary or systemic blood flow was entirely or significantly dependent upon the patency of the ductus arteriosus. In 12 patients with pulmonary atresia or severe pulmonary stenosis, PGE1 infusion was followed by an improvement in hypoxemia and acidemia (group I). In 2 patients with left ventricular outflow-tract obstruction, PGE1 infusion was followed by an improvement in arterial blood pressure, peripheral perfusion and urine output (group II). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
1
7
1
Order By: Relevance
“…Our incidence of apnea was within the range of other reports [7][8][9]11], and mechanical ventilation for prolonged apnea was not necessary for any of our patients. One-fourth of all neonates to whom PGE 1 is administered will experience apnea, highlighting the need for close cardiopulmonary monitoring of these patients in an intensive care, intermediate care, or neonatal unit.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our incidence of apnea was within the range of other reports [7][8][9]11], and mechanical ventilation for prolonged apnea was not necessary for any of our patients. One-fourth of all neonates to whom PGE 1 is administered will experience apnea, highlighting the need for close cardiopulmonary monitoring of these patients in an intensive care, intermediate care, or neonatal unit.…”
Section: Discussionsupporting
confidence: 85%
“…In the study of Lewis et al [7], central nervous system events were observed more often in acidotic patients and in those with a longer duration of PGE 1 infusion. The highest incidence of seizure-like activities was noted in the study of Ohara et al [9], but it is not obvious from this study whether these patients had additional risk factors such as asphyxia or prematurity.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Prostaglandin E1 was introduced in the late 1970s 10 and widely used in the 1980s in Japan, 11 contributing to better management of neonates with ductaldependent critical CCVM. At the same time, 2-dimensional echocardiography was introduced and widely used in 1980s in Japan, 12 dramatically changing non-invasive diagnostic accuracy, especially for neonatal CCVM.…”
Section: Population-based Mortalitymentioning
confidence: 99%
“…2 It is assumed that with ductal reopening, clinical signs improve and RV function normalizes. [3][4][5] This improvement in RV function has not been prospectively quantitated in patients with HLHS. Likewise, the impact of initial surgical palliation on RV function in this patient population has not been measured.…”
Section: Introductionmentioning
confidence: 99%